INCREASING ECONOMIC CAPABILITY: ECONOMIC PERFORMANCE STRATEGY IN UYGHUR - Ratna Sari Dewi; Anggia Sari Lubis; Shita Tiara; Hardi Mulyono; Firmansyah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
A comprehensive economic performance strategy to address the dual hurdles of countries such as Uyghur, encompassing structural transformations and market imperfections. Upon scrutinizing the conditions that slow development in Uyghur, we can make a series of fundamental changes with regards to the local value chain as well the overall economy. The outcome of this study is the recommendations on how to increase the economic capability as well as formulating economic performance strategy in Uyghur. The recommendations are: (1) Improving government efficiency by improving decision making, (2) Regulating an open and favorable trade environment which enhances capabilities in international markets, (3) improving productivity, (4) Improving educational systems to offer quality education, (5) Encouraging human development strategies by reducing poverty and inequality, reduces unemployment rates, fostering growth through domestic entrepreneurship, Hence, transforming economies in Uyghur must involve the improvement of local capabilities throughout international value chains, institutional reforms, innovations in human capital formation, also well as effective redistribution of resources.